Dendritic cell-mediated vaccination relies on interleukin-4 receptor signaling to avoid tissue damage after Leishmania major infection of BALB/c mice. - Anita Masic; Ramona Hurdayal; Natalie E Nieuwenhuizen; Frank Brombacher; Heidrun Moll (Public Library of Science (PLoS), 2012)
Prevention of tissue damages at the site of Leishmania major inoculation can be achieved if the BALB/c mice are systemically given L. major antigen (LmAg)-loaded bone marrow-derived dendritic cells (DC) that had been exposed to CpG-containing oligodeoxynucleotides (CpG ODN). As previous studies allowed establishing that interleukin-4 (IL-4) is involved in the redirection of the immune response towards a type 1 profile, we were interested in further exploring the role of IL-4. Thus, wild-type (wt) BALB/c mice or DC-specific IL-4 receptor alpha (IL-4Rα)-deficient (CD11c(cre)IL-4Rα(-/lox)) BALB/c mice were given either wt or IL-4Rα-deficient LmAg-loaded bone marrow-derived DC exposed or not to CpG ODN prior to inoculation of 2×10⁵ stationary-phase L. major promastigotes into the BALB/c footpad. The results provide evidence that IL4/IL-4Rα-mediated signaling in the vaccinating DC is required to prevent tissue damage at the site of L. major inoculation, as properly conditioned wt DC but not IL-4Rα-deficient DC were able to confer resistance. Furthermore, uncontrolled L. major population size expansion was observed in the footpad and the footpad draining lymph nodes of CD11c(cre)IL-4Rα(-/lox) mice immunized with CpG ODN-exposed LmAg-loaded IL-4Rα-deficient DC, indicating the influence of IL-4Rα-mediated signaling in host DC to control parasite replication. In addition, no footpad damage occurred in BALB/c mice that were systemically immunized with LmAg-loaded wt DC doubly exposed to CpG ODN and recombinant IL-4. We discuss these findings and suggest that the IL4/IL4Rα signaling pathway could be a key pathway to trigger when designing vaccines aimed to prevent damaging processes in tissues hosting intracellular microorganisms.